Module Development: Psychological-Based Prehabilitation for Breast Cancer Patients and their Family Caregivers - Yoke Yong, Chen; Huey Szee, Saw (Cambridge University Press, 2025)
Introduction: Cancer prehabilitation has emerged as a pivotal Strategy for the augmentation of patients’ comprehensive wellbeing, encompassing physical, psychological, and functional aspects while improving their quality of life. The profound impact Of breast cancer on patients and their family caregivers emphasizes the critical need for interventions addressing their holistic wellbeing. Objectives: In this portion of the study, researchers intend to develop two psychological-based prehabilitation modules within a larger investigation targeting to address the quality of life as well as relationship quality among breast cancer patients and their family Caregivers. The deliberate involvement of the family caregiver Proposed here is based on the belief that the well-being of an individual is interconnected with his/her community.